A Feasibility Study for Housing Allowances from The Bandung Regency DPRD - Farhan Rahmawan Halim; Mubarok Mubarok; Rina Mutiarawati (Publica: Jurnal Pemikiran Administrasi Negara, 2021)
An amendment to Regent Regulation Number 60 of 2017 concerning the Amount of Housing Allowances and Transportation Allowances for Leaders and Members of the Bandung Regency DPRD is regulated in Bandung Regent Regulation Number 23 of 2020, indicating that the percentage of increase in housing allowances for both leaders and members, where overall is above 30%. This is what underlies this research. The purpose of conducting this research is to test the appropriateness of the Bandung Regency DPRD allowances for changes in the amount of housing allowances. The method of calculation and data analysis used is to use attachment IIA of Regulation of the Minister of Finance Number 96 / PMK.06 / 2007 and also to use a macroeconomic approach by taking into account Government Regulation Number 18 of 2017 Article 17 which states that in determining it must consider the principles of appropriateness, reasonableness, rationality, standard local prices. The results showed that the change in the amount of allowance made by the Regional Government of Bandung Regency was quite large. This is because the advantages of providing allowances provided by the Regional Government to the Bandung Regency DPRD can actually be a loss, not only for the Bandung Regency area, but for the state. This can be seen from the difference in the calculation results, if multiplied by the number of board members, the number that comes out will be quite large